The first global 883 GHz cloud ice survey: IceCube Level 1 data calibration, processing and analysis - J. Gong (Copernicus Publications, 2021)
Sub-millimeter (200–1000 GHz) wavelengths contribute a unique capability to fill in the sensitivity gap between operational visible–infrared (VIS–IR) and microwave (MW) remote sensing for atmospheric cloud ice and snow. Being able to penetrate clouds to measure cloud ice mass and microphysical properties in the middle to upper troposphere, a critical spectrum range, is necessary for us to understand the connection between cloud ice and precipitation processes.